Develop a drive assistant system to improve dynamic stability and safety of vehicle - Awiwi, Rami; Abu Turki, Khaleel; Najajrah, Salem; Sarahneh, Awfa (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2022)
The general objective of the project is improve safety for passenger during travel by develop a system based on guiding the driver to determine the appropriate speed and steering angle based on the diminution of the road and the specification of the vehicle such as (weight, distance between the two wheels...etc.), and the actual vehicle information such as speed, wheel steering angle and vehicle coordinates collected. It enters into calculations in order to achieve the main goal of avoiding loss control of vehicle accident and deviating from the lane. In this project, we relied on several auxiliary technologies, such as Global Positioning System GPS, which helps to know the actual location and coordinates of the vehicle, and the Geographic Information System GIS, which helps to know general information about the road such as turns, road length and width, and finally Electronic Control Unit ECU, where extract the information from the electronic control unit such as speed and steering angle, and finally using the vehicle dynamics equations that work to calculate the appropriate speed of the vehicle and the appropriate angle of turning based on the previous inputs. The simulation process was carried out by MATLAB program. In this project, the actual reading was taken from the electronic control unit in the vehicle and the location of the vehicle. and linked in MATLAB After the experiment and make many sample of same rod (inside the university), take 190 value for vehicle speed, steering angle, longitude and latitudes data, then after Data processing by matlab the simulation result for vehicle speed and steering angle command is very reliable .
no of pages 130, هندسة حاسوب 16/2022
Keywords: a drive assistant systems